ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERKUNJUNG WISATAWAN DI SENDANG SUMBER SEGARAN DESA.SUKILILO-KEC.PRIGEN- KABUPATEN PASURUAN - uddin, Moch. taufik sholeh; Itsna Hidayati, Novi; Lidyana, Novita (Agrotechbiz : Jurnal Ilmiah Pertanian, 2024)
This research aims to examine the interest of tourists visiting the tourist destination of Sendang Sumber Segaran. The random sampling technique was used for the selection of the sample of this study with the sample to be studied was 50 visitors in the range of 40-60 weeks. The Cochran Q Test method was used as a method in this study. The findings from this study describe several factors that affect the interest of tourists who come to the Sendang Sumber Segaran tourist destination, namely there are 5 questions that affect the interest of tourists to visit, namely natural beauty (p1), natural tourist attractions (p2), excellent tourist service (p6), invited friends (p7), being able to take pictures (p10). There are the most dominant factors of several factors, namely the highest score in answering YES in influencing tourists' interest in visiting. Not only is this destination an ideal choice for family vacations thanks to its spacious seating facilities, but it also provides educational experiences such as feeding and bathing goats, making it an attractive and varied tourist attraction for visitors, among others. This destination offers an amazing tourist experience with high tourism, featuring various forms of natural beauty, interesting ecosystems, and natural springs. Keywords: Tourist attraction, Visitor interest, Sendang Sumber Segaran